Probability of major depression diagnostic classification based on the SCID, CIDI and MINI diagnostic interviews controlling for Hospital Anxiety and Depression Scale - Depression subscale scores: An individual participant data meta-analysis of 73 primary studies - Wu, Y; Levis, B; Sun, Y; Krishnan, A; He, C; Riehm, KE; Rice, DB; Azar, M; Yan, XW; Neupane, D; Bhandari, PM; Imran, M; et al. (Elsevier, 2019)
Objective Two previous individual participant data meta-analyses (IPDMAs) found that different diagnostic interviews classify different proportions of people as having major depression overall or by symptom levels. We compared the odds of major depression classification across diagnostic interviews among studies that administered the Depression subscale of the Hospital Anxiety and Depression Scale (HADS-D).